Dopaminergic inhibition of human neutrophils is exerted through D1‐like receptors and affected by bacterial infection. Issue 4 (24th August 2022) - Marino, Franca; Pinoli, Monica; Rasini, Emanuela; Martini, Stefano; Luini, Alessandra; Pulze, Laura; Dalla Gasperina, Daniela; Grossi, Paolo; Legnaro, Massimiliano; Ferrari, Marco; Congiu, Terenzio; Pacheco, Rodrigo; et al.
Abstract: Dopamine (DA) affects immune functions in healthy subjects (HS) and during disease by acting on D1‐like (D1 and D5) and D2‐like (D2, D3 and D4) dopaminergic receptors (DR); however, its effects on human polymorphonuclear leukocytes (PMN) are still poorly defined. We investigated DR expression in human PMN and the ability of DA to affect cell migration and reactive oxygen species (ROS) production. Experiments were performed on cells from HS and from patients (Pts) with bacterial infections as well, during the acute phase and after recovery. Some experiments were also performed in mice knockout (KO) for the DRD5 gene. PMN from HS express both D1‐like and D2‐like DR, and exposure to DA results in inhibition of activation‐induced morphological changes, migration and ROS production which depend on the activation of D1‐like DR. In agreement with these findings, DA inhibited migration of PMN obtained from wild‐type mice, but not from DRD5KO mice. In Pts with bacterial infections, during the febrile phase D1‐like DRD5 on PMN were downregulated and DA failed to affect PMN migration. Both D1‐like DRD5 expression and DA‐induced inhibition of PMN migration were however restored after recovery. Dopaminergic inhibition of human PMN is a novel mechanism which is likely to play a key role in the regulation of innate immunity. Evidence obtained in Pts with bacterial infections provides novel clues for the therapeutic modulation of PMN during infectious disease. Abstract : Dopaminergic receptors (DR) are expressed on human polymorphonuclear leukocytes (PMN) and their expression is regulated upon PMN activation. Dopamine (DA) inhibits PMN functional responses through D1‐like DR‐operated pathways in both humans and wild‐type mice but not in DRD5KO mice. In patients with bacterial infections, D1‐like DRD5 expression on circulating PMN is reduced and DA fails to inhibit PMN migration during the acute phase of infection, and both conditions are restored after recovery.